Temperament and Character Dimensions of Personality in Individuals with Online Gambling Disorder in a High School Student Sample from Turkey - (:unkn) unknown (TURKISH ASSOC PSYCHOPHARMACOLOGY, 2020)
Background: The present study aimed to examine the relationship between online gambling addiction, temperament, and attachment styles in an adolescent sample in Istanbul, Turkey. Methods: The participants of the study consisted of 790 adolescents who are high school students. Sociodemographic information of the participants was collected, and Temperament and Character Inventory - Turkish Version (Turkish-TCI), Relationship Scales Questionnaire (RSQ), Specific Internet, Online Gambling and Online Sexuality Addiction Scale were administered. All statistical analyses were performed using IBM SPSS Statistics (Statistical Package for the Social Sciences) 24.0 for Windows (SPSS Inc., Chicago, IL, USA). All variables were screened for accuracy of data entry, missing values, and homoscedasticity. Results: Online gambling addiction scores were significantly higher in male participants (M = 1.83, SD = 1.09) compared to female participants (M = 1.28, SD = 0.67). A statistically significant difference was found when the online gambling addiction mean scores were compared in terms of maternal education level of the participants [F (5,666) = 2.82, p < 0.05, h2 = 0.021]. It has been observed that sentimentality, which is one of the temperamental features, contributes 2.3% to the total variance in addition to age and average daily internet usage, negatively and significantly predicting online gambling addiction (beta = - 0.163, p < 0.01). All three variables together explained 9.1% of the total variance. Furthermore, study results revealed statistically significant correlations between online gambling addiction scores and Secure (r = 0.09, p < 0.05) and Preoccupied (r = 0.10, p < 0.05) subscales of the RSQ. Conclusions: Online gambling addiction was predicted by sentimentality subscale of Reward Dependence, and it was related to Secure and Preoccupied attachment styles. Sentimentality subscale of Reward Dependence (RD) was found to be a significant predictor of online gambling addiction.
Keywords: online gambling; addiction; temperament; TCI; relationship scales questionnaire (RSQ)